Experimental investigation on the effect of wettability on rock-electricity response in sandstone reservoirs. (1st March 2019) - Han, Yujiao; Zhou, Cancan; Yu, Jun; Li, Chaoliu; Hu, Falong; Xu, Hongjun; Yuan, Chao
Abstract: To fundamentally study the effect of wettability on sandstone conductivity, a series of experiments, including rock-electricity, nuclear magnetic resonance (NMR) and wettability tests, were conducted systematically on high- and low-permeability sandstone samples. The results show that wettability had different influence on the conductivity laws of high- and low-permeability sandstones, which was mainly caused by the complex combination of pore and pore-throat. The conductivity laws of oil-wet high-permeability sandstones, which mainly developed large pores and coarse throats with small water-wet bound space, were mainly followed the oil-wet conduction law. However, the preferentially oil-wet low-permeability sandstones primarily developed middle-to-small pores and micro throats with large water-wet bound space. Hence, the large amount of bound space followed the water-wet conduction law, while the relatively large pore with oil-wet property was dominated by oil-wet conduction law. Consequently, the conductivity of oil-wet sandstones with low-permeability was co-controlled by the wettability and pore structure. The study can result in a quite different saturation under the same resistivity compared with the Archie's law, and provide a meaningful guidance for establishing oil-saturation calculation model, which can improve the oil-layer identification accuracy and eventually enhance the oil-wet reservoir recovery.